An Introduction to Including Individuals with Special Needs in the Garden - Jessica Williams; Paul Monaghan; Ricky Telg; Shelley Voelker (EDIS)
Whether at a farm, garden, school, Extension program, or even at home, working with plants comes with the need for safety, accessibility, and specific instruction style. This new 7-page publication of the UF/IFAS Department of Agricultural Education and Communication provides information on each of these areas as well as suggested programs and activities. This document can be useful to Extension agents, special and general educators, or parents who have an interest in gardening with their students or children; and those working with volunteers who have special needs. Written by Jessica Williams, Paul Monaghan, Ricky Telg, and Shelley Voelker. https://edis.ifas.ufl.edu/wc403